Studies on the Characterisation and Utilisation of a New Phytase-Producing Bacterium Isolated from the Rumen of Cattle - Ganqiu, Lan (2001)
Five phytase-producing bacterial strains isolated from the rumen of cattle were identified to be a new bacterial species based on their morphological, physiological, biochemical and molecular characters. The new species is named Mitsuokella jalaludinii. Mitsuokella jalaludinii hydrolysed sodium phytate rapidly and the phytase production was strongly induced by phytate present in the medium. Rice bran (RB) and soybean milk (SM) were found to be the best carbon and nitrogen sources, respectively, for phytase production by M. jalaludinii. Phosphate at a level of 0.05 - 0.5% in RB -SM medium had no effect on phytase production. Glucose added to RB-SM medium had a negative effect on phytase production of M jalaludinii. The optimum temperature and optimum initial pH for phytase production of M jalaludinii were 3 9 °C and about 7.0, respectively. The activity of M jalaludinii phytase was highest at 55 - 60°C and pH 4.0 - 5.0. It was specific to phytate as a substrate, significantly stimulated by Ba2+, Mn2+, and Ca2+ and significantly inhibited by Zn2+, Cu2+, Fe2+ and Fe3+. The metal ion chelators and phosphate were not the inhibitors of M jalaludinii phytase activity. Acute pathogenicity tests indicated that M jalaludinii was non-pathogenic to chickens and mice. Supplementation of M jalaludinii culture to corn soybean meal feed for chickens significantly increased P released from the feed in vitro and P, DM and CP digestibilities in vivo. About 70% of in vivo response in P digestibility and 90% of in vivo response in DM and CP digestibilities or AME value could be predicted by the P released in vitro. Mitsuokellajalaludinii phytase was most active in the crop of broiler chickens and was inactivated in the stomach. Supplementation of either fresh active M jalaludinii culture (AMJC) or freezedried active M jalaludinii culture (FD-AMJC) or Natuphos® phytase to 10w-aP diet significantly improved the feed intake, body weight gain and feed conversion ratio of broilers. The digestibilities of DM, CP, P , Ca, and Cu and the AME value of diet were significantly increased by the supplementation of AMJC. S upplementation of AMJC or FD-AMJC or Natuphos® phytase to 10w-aP diet significantly increased the tibia ash content and serum P concentration but significantly reduced Mn concentration in tibia ash of broiler chickens. Chicks receiving FD-AMJC had better (P<0.05) feed conversion rate as compared to those receiving Natuphos® phytase. FD-AMJC supplementation to 1 0w-aP diet significantly (P<O.OS) increased the AME value of diet and the digestibilities of DM, CP, P, Ca and Cu ( 1 1 to 1 3 - day-old and 1 8 to 20-day-old chicks) but Natuphos® phytase supplementation only significantly improved the digestibilities of DM, P ( 1 1 to 1 3 -day-old and ] 8 to 20- day-old chicks) and Ca ( 1 1 to 1 3 -day-old chicks). Chicks receiving 10w-aP diet added with AMJC or FD-AMJC or Natuphos® phytase had similar (P>0 .05) performance as those receiving normal-aP diet but excreted less (P<0.05) phosphorus.